Immunomodulatory role of mesenchymal stem cell therapy in liver fibrosis - Liu, Peng; Qian, Yerong; Liu, Xin; Zhu, Xulong; Zhang, Xufeng; Lv, Yi; Xiang, Junxi (Frontiers in Immunology, 2023)
Liver fibrosis is a fibrogenic and inflammatory process that results from hepatocyte injury and is characterized by hepatic architectural distortion and resultant loss of liver function. There is no effective treatment for advanced fibrosis other than liver transplantation, but it is limited by expensive costs, immune rejection, and postoperative complications. With the development of regenerative medicine in recent years, mesenchymal stem cell (MSCs) transplantation has become the most promising treatment for liver fibrosis. The underlying mechanisms of MSC anti-fibrotic effects include hepatocyte differentiation, paracrine, and immunomodulation, with immunomodulation playing a central role. This review discusses the immune cells involved in liver fibrosis, the immunomodulatory properties of MSCs, and the immunomodulation mechanisms of MSC-based strategies to attenuate liver fibrosis. Meanwhile, we discuss the current challenges and future directions as well.